The Long-Acting Ca2+-Channel Blocker Azelnidipine Prevents Left Ventricular Remodeling After Myocardial Infarction - Daisuke Nishiya; Soichiro Enomoto; Takashi Omura; Ryo Matsumoto; Takanori Kusuyama; Yasukatsu Izumi; Hiroshi Iwao; Kazuhide Takeuchi; Minoru Yoshiyama (Elsevier, 2007)
Long-acting Ca2+-channel blockers have been reported to be effective in treating ischemic heart disease. However, their effects on cardiac remodeling after myocardial infarction (MI) are still unclear. We performed this study to examine the effect of azelnidipine on left ventricular (LV) remodeling, including systolic and diastolic dysfunction, in rats with MI. MI was induced by ligation of the left anterior descending artery. The rats were then separated into 3 groups: a sham-operated group (n = 9), untreated MI group (n = 10), and azelnidipine-treated MI group (n = 10). Four weeks after MI, hemodynamic measurements and Doppler echocardiographic assessment were performed. LV weight and LV end-diastolic dimension were significantly higher in the untreated MI group than in the sham-operated group. Azelnidipine significantly prevented the increases in these parameters. Azelnidipine also improved the ejection fraction (42 ± 3%, P<0.05) and the E wave to A wave ratio (3.2 ± 0.5, P<0.05), compared with the untreated MI group (31 ± 3% and 5.3 ± 0.8, respectively). In conclusion, azelnidipine can prevent LV remodeling and improve systolic and diastolic function after MI. Administration of long-acting Ca2+-channel blockers after MI is an effective strategy for treating MI. Keywords:: calcium channel blocker, myocardial infarction, cardiac remodeling, ventricular function, gene expression